Improving TB Surveillance and Patients' Quality of Care Through Improved Data Collection in Angola: Development of an Electronic Medical Record System in Two Health Facilities of Luanda - Robbiati, Claudia; Tosti, Maria Elena; Mezzabotta, Giampaolo; Dal Maso, Francesca; Lulua Sachicola, Ofélia M.; Siene Tienabe, Paulo; Nsuka, Joseph; Simonelli, Marco; Dente, Maria Grazia; Putoto, Giovanni (Frontiers in Public Health, 2022)
TB Programs should promote the use of digital health platforms, like Electronic Medical Records (EMR) to collect patients’ information thus reducing data incompleteness and low accuracy and eventually improving patients care. Nevertheless, the potential of digital health systems remains largely unexploited in low-resource settings. Angola is one of the 14 countries with a triple burden of TB, TB/HIV and MDR-TB (multidrug-resistant TB) and is among the three countries, together with Congo and Liberia that have never completed a drug-resistance survey so far. The Sanatorium Hospital of Luanda and the Tuberculosis Dispensary of Luanda are the two reference health facilities in Luanda dealing with most of the TB cases, and they both rely entirely on paper-based patients’ data collection. The aim of this paper is to describe a three-stage process for the development of a TB EMR system in these two health facilities of Luanda and share the lessons learned. The description is focused on the activities that took place from March 2019 to January 2020. Main lessons learned were identified in the importance of engaging all the stakeholders in the development process, in the mainstream of the “think digital” transition, in the promotion of a monitoring and evaluation (M&E) culture and in the planning of the system sustainability. This approach may be replicated in similar contexts where the development of a TB EMR system is sought and the lessons learned could assist and facilitate the programming of the interventions.